2011
DOI: 10.1007/s00125-011-2075-y
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of foot risk predicts the incidence of new foot disease, but do we yet know that the adoption of routine screening reduces it?

Abstract: The evidence to justify classifications of foot risk is derived from a number of large cross-sectional and prospective studies, and is very strong: it is possible to identify clinical features of the individual patient that are linked to the relative risk of future ulceration. The presence of peripheral arterial disease, neuropathy or deformity will increase the risk modestly, while any combination of these will increase it more and the risk is highest in those with a history of previous foot disease or surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 12 publications
2
26
0
2
Order By: Relevance
“…Despite these modifications and using all the different definitions proposed, these two variables were highly associated with DFU development (P!0.001). This corroborates our systematic review results: DPN and PVD clinical collection methods seem relatively unimportant (4,15). Although several authors have described the foot pulse palpation to have low sensitivity (16,17), the SWM application procedure does not have consensus (18,19) and the tuning fork has low reliability (19); several studies have shown that these simple methods can be implemented for both community (2,8,15,19,20) and high risk (3, 4) setting diabetic foot screening, independently of the variables collection method.…”
Section: Discussionsupporting
confidence: 86%
“…Despite these modifications and using all the different definitions proposed, these two variables were highly associated with DFU development (P!0.001). This corroborates our systematic review results: DPN and PVD clinical collection methods seem relatively unimportant (4,15). Although several authors have described the foot pulse palpation to have low sensitivity (16,17), the SWM application procedure does not have consensus (18,19) and the tuning fork has low reliability (19); several studies have shown that these simple methods can be implemented for both community (2,8,15,19,20) and high risk (3, 4) setting diabetic foot screening, independently of the variables collection method.…”
Section: Discussionsupporting
confidence: 86%
“…18 Clinically effective and cost-effective health care requires the careful measurement of health outcomes, and the need for an evidence-based approach to foot care services in diabetes has been documented. 19,20 Two systematic reviews highlight the gaps in the knowledge about the best way to identify those at risk.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…Det anses som viktig med individuell opplaering (Jeffcoate WJ, 2011). For den enkelte pasient er tiltaket daglig å undersøke føttene.…”
Section: Verdier Og Preferanserunclassified